MATHEMATICAL MEANING IN MODELLING CONTEXT THROUGH THE ONTO-SEMIOTICS APPROACH - Umam, Khoerul; Nusantara, Toto; Parta, I Nengah; Hidayanto, Erry (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
The main objective of this research will implement the onto-semiotics approach to analyse the conceptual of mathematical meaning in a modelling context corresponding to their use of the mathematical objects. Semiotics functions and mathematical object that emerged when solving mathematical modelling will be highlighted according to OSA. Students responses to modelling questions were used to classify the semiotics function that relates to the different mathematical objects.